Chlorophytum vanapushpam (Asparagaceae), a new species from southern Western Ghats, India - Nair, Sidharth Sathyan; Mathew, Jose; Narayanan, Matalayi Kokaramath Ratheesh; Sanilkumar, Malayil Gopalan; Sunil, Chandrasseril Narayanan (Phytotaxa, 2025)
Within the context of the floristic study of tuberous plants of south Western Ghats, a new species, Chlorophytum vanapushpam is described. This species resembles C. glaucoides Blatter (1931: 361) but differs in many other characters, viz., cylindrical fusiform spongy roots, sessile broad leaves, long scape, ovate bracteoles with acute apex, 5-nerved outer perianth segments and 3–5-nerved inner perianth segments, anthers are slightly shorter than its filaments and seeds are large, 3–4 in each cells. The taxonomic description, morphological differences to allied taxa, key to the Indian Chlorophytum and colour photographs of the new species are provided to facilitate its easy identification in the field.